Case report: Acquired neurotrophic tyrosine receptor kinase inhibitor resistance in a patient with pancreatic neuroendocrine carcinoma receiving entrectinib - Wu, Wen-Chi; Chen, Ming-Huang (Frontiers in Oncology, 2023)
Pancreatic neuroendocrine carcinoma (panNEC) was a rare disease. The rearrangements of neurotrophic tropomyosin receptor kinase (NTRK) genes were oncogenic, and the prevalence of NTRK3 was only 0.1% in neuroendocrine tumors. NTRK inhibitor was approved for refractory and recurrence NTRK fusion-positive solid tumors did not respond to standard treatment. We described a patient with panNEC who was confirmed to have ETV6-NTRK3 fusion gene by liquid biopsy. The patient initially responded well to entrectinib, a first-generation NTRK inhibitor, but developed resistance with two acquired NTRK3-G623R and NTRK3-G623E mutations detected by a second liquid biopsy. Kirsten rat sarcoma vial oncogene (KRAS) K117N mutation was found initially but became undetectable after resistance. This was the first report demonstrating the novel agent, entrectinib, used for the NTRK3-fusion gene found by the liquid biopsy in panNEC. Our report provides evidence of not only the effectiveness but also the acquired resistance of entrectinib. Also, we highlighted the potential role of genomic sequencing after entrectinib failure. Furthermore, liquid biopsy should be considered if acquiring tissue from the patient is challenging. Further studies regarding NTRK inhibitors in panNEC were needed.